On uniform statistical convergence of random variable sequences - Gungor, Mehmet; Gokhan, Ayşegül (Türkmenoglu) (My University, 2009)
In this study, we introduce a notion of uniform statistical convergence of random variable sequences. We show that a continuous function conserves the limit of statistical convergence of real-number sequences. Furthermore we introduce the concept of a uniform statistically Cauchy sequence for random variables and prove that it is equivalent to uniform statistical convergence of sequences of random variables.
Keywords: Random variable sequence; Statistical convergence; Uniform convergence; Uniform statistical convergence